Exploring the experiences and implementing strategies for physiotherapy students who perceive they have been bullied or harassed on clinical placements: participatory action research. Issue 1 (March 2017) - Thomson, Di; Patterson, David; Chapman, Hannah; Murray, Louise; Toner, Maeve; Hassenkamp, Anne-Marie
Abstract: Objectives: To explore and empower physiotherapy students who reported being bullied or harassed on clinical placements by co-developing, implementing and evaluating strategies that could be adopted by the university. Design: A participatory action research design was employed. Participants: Two focus groups were carried out involving 5 final year physiotherapy students. In the first focus group negative experiences were discussed and coping strategies suggested for their penultimate placement. A second focus group was held following the students' final placement when these strategies were evaluated and further ones proposed. Analysis: A thematic analysis of the data was carried out. Results: Four themes and sub-themes emerged from the analysis. The four themes were negative experiences on placement, coping strategies, the role of the visiting tutor and the assessment. The students' highlighted various degrees of threat to their efficacy and in most cases could draw upon a suggested 'tool box' of coping strategies. They all agreed that serious cases of harassment require wider support from the University senior management team which should be clearly documented. The role of the visiting tutor was deemed to be critical in these situations and recommendations were made regarding this role and the assessment of placements. Conclusion: Students understand that they are going to be assessed before achieving their professional qualification and in essence they will always find themselves in a hierarchical position but equally fairness must prevail and it is important and that there are clear avenues for them to seek support.